PROOXIDANT-ANTIOXIDANT HOMEOSTASIS IN SPERM OF BREEDING BOARS WITH DIFFERENT TYPES OF HIGHER NERVOUS ACTIVITY - Stoianovskyi, V. G.; Usenko, S. O.; Shostya, A. M.; Bereznytskyi, V. I.; Usenko, O. O.; Slynko, Ye. V. (Scientific Progress & Innovations, 2020)
The peculiarities of types of higher nervous activity influence on the formation of pro-oxidant-antioxidant homeostasis in the ejaculates of breeding boars have been studied. Using motor-nutritional techniques, adult breeding boars of the Large White breed aged 24–36 months were distributed according to the main types of higher nervous activity. Four groups of 3 heads in each were formed. The first group included animals of a strong balanced lively (mobile) type; group II - a strong balanced calm (inert); group III - strong unbalanced (unrestrained); group IV – weak types of higher nervous activity. Sperm was obtained from breeding boars manually dividing the ejaculate into 4 fractions: F1 – the first, F2 – the second, F3 – the third, F4 – the fourth. It has been found out that the indexes of sperm production and the course of peroxidation processes in in breeding boars are determined by the type of their higher nervous activity (HNA). In animals of strong unbalanced and weak types of HNA, the peroxidation process is more intensive, the antioxidant protection system is at a lower level – less superoxide dismutase activity (p<0.05), lower concentration of ascorbic acid (p<0.001), vitamin A (p<0.01–0.001) and vitamin E (p<0.001). At the same time, ejaculate mass and sperm saturation in individuals of weak HNA type was minimal (p<0.001). It has been found that sperm saturation significantly affects the course of peroxidation processes. Spermatozoa from the second ejaculate fraction were characterized by the highest survival ability, while in the third one they quickly lost functional activity. The sperm functional activity and peculiarities of PAH formation depend on types of HNA – acceleration of peroxidation processes is probable in strong unbalanced and weak types because of higher concentration of diene conjugates and dehydroascorbic acid. In animals with strong balanced lively and calm types of HNA, a higher level of antioxidant protection was registered as a result of catalase and superoxide dismutase activity, the amount of reduced glutathione, ascorbic acid and vitamin E. In the first and fourth ejaculate fractions, SOD activity, vitamin A and vitamin E were absent, which determined low functional activity and sperm survival ability. These fractions from a strong unbalanced and weak types of HNA were characterized by a probably higher content of DC (p<0.05–0.01) and TBA-active complexes (p<0.05–0.001), as well as a lower amount of AA (p<0.01), reduced glutathione (p <0.05) and SOD activity.